Modified artificial fish swarm algorithm to solve unrelated parallel machine scheduling problem under fuzzy environment - Azhar Mahdi Ibadi; Rosshairy Abd Rahman (AIMS Mathematics)
Unrelated parallel machine scheduling problem (UPMSP) in a fuzzy environment is an active research area due to the fuzzy nature of most real-world problems. UPMSP is an NP-hard problem; thus, finding optimal solutions is challenging, particularly when multiple objectives need to be considered. Hence, a metaheuristic algorithm based on a modified artificial fish swarm algorithm (AFSA) is presented in this study to minimize the multi-objective makespan and total tardiness. Three modifications were made to the proposed algorithm. First, aspiration behavior was added to AFSA behaviors to increase effectiveness. Second, improved parameters such as step and visual were used to balance global search capability and convergence rate. Finally, a transformation method was injected to make the algorithm suitable for discrete optimization problems such as UPMSP. The proposed algorithm was compared with AFSA and five modified versions of AFSA to verify and measure the algorithm's effectiveness by conducting three different sizes of problems. Afterward, the Wilcoxon signed-rank test was used to statistically evaluate the algorithm's performance. The results indicate that the proposed algorithm significantly outperformed the other algorithms, especially for medium and large-sized problems.